Ta'tsīr Barnāmaj Fatḥ al Kutub 'alā Targīb al Ta‘allum al-Dzātī li Ṭālibāt al Ṣaff al Khāmis Ma‘had Dār al Salām Gontor al Ḥaram al Tsālits lil-Banāt. - Mulyanto, Dedi; Kaltsum, Nisrina Aini (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2025)
This study examines the impact of the Fathu Kutub at-Turats program on students' interest in self-directed learning, particularly in enhancing Arabic reading and writing skills. Conducted at Darussalam Gontor Islamic Boarding School Third Campus for Girls, the research employs a quantitative survey approach. Data was collected through written documentation and questionnaires, with a total population of 420 fifth-grade students and a sample of 80 students selected using quota sampling. The results indicate a statistically significant relationship between the Fathu Kutub at-Turats program and students' interest in self-directed learning. The correlation coefficient (R) of 0.699 shows a moderate to strong positive relationship, and the coefficient of determination (R²) of 0.489 means that 48.9% of the differences in self-directed learning are due to the program, while the other 51.1% are affected by other factors. These findings reinforce the role of the Fathu Kutub at-Turats program as an effective approach to fostering independent learning and enhancing Arabic literacy skills. The study underscores the program’s contribution to promoting self-directed learning and supports its continued implementation as a strategy for developing linguistic proficiency.